Eyelash Extension dalam Perspektif Hukum Islam - Iskandar, Iskandar; Sari, Hijrayanti; Atika, Nurul (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2020)
This study aimed to identify the law of using eyelash extensions from the perspective of Islamic law, as well as what the scholars think about it. To get answers to this problem, descriptive qualitative research (non-statistical) was used which focused on the study of texts and texts and used historical and phenomenological approaches. The research results found are; First, eyelash extension is a method of lengthening and adding lashes with the aim of adorning or beautifying the eyes. Second, the eyelash extension procedure is done by gluing the lashes together with the original perimeter lashes using a special glue. As for the impact of eyelash extensions, it causes eyelashes to fall out, irritation, allergies, and eye injuries. Third, in determining the law of eyelash extensions from an Islamic perspective, the authors explore the law by applying eyelash extensions to the hair, and in this case, the scholars have different opinions. If real (human) hair is used, the majority of scholars forbid it. As for using synthetic hair, the scholars have different opinions, some permit while some others absolutely prohibit using either real hair or synthetic hair, and there are also those who differentiate the law by seeing whether the woman is married or not. If a woman is not married, it is not allowed, as for those who